Spain : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2015)
This Selected Issues paper presents a preliminary assessment of recent labor market reforms in Spain, where the 2012 labor market reforms are making a difference. Wage moderation is contributing to a visible recovery in headline employment growth, and the reforms have made the labor market more resilient to shocks. Some evidence exists that the contribution of temporary contracts to employment growth has started to decrease. However, the reliance on temporary workers remains strong overall, and further structural reforms will be required to reduce the still very high level of long-term, structural unemployment.